Teacher Knowledge as Context - Drew S. Fagan (Working Papers in Applied Linguistics and TESOL, 2015)
Research has shown that teachers bring into the classroom multiple domains of knowledge, including disciplinary knowledge, pedagogical content knowledge (i.e., the process of relaying disciplinary knowledge to students), knowledge of how learning occurs, knowledge of students’ learning styles, knowledge of curricular and contextual demands, their own personal practical knowledge (e.g., experiences in the classroom as a student; cultural norms surrounding the role of a teacher), and knowledge of how to reflect on all of these domains in order to adapt one’s teaching accordingly. This piece will briefly explain and demonstrate the importance in examining teacher knowledge as context within classroom discourse analysis in order to enrich the understanding of what is happening in classroom interaction and explain why it is so.